MANFAAT BIAYA KUALITAS DALAM UPAYA PENINGKATAN PRODUKTIVITAS PERUSAHAAN - Kusumawati, Rika (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
This research is meant to comprehend whether the quality cost will be useful in order to improve the companyâs productivity and to analyze the influence of quality cost to the use of raw materials. By using PT Gunawan Dian Jaya Steel as the subject of the research, the quality costs are the subject of analysis which consists of prevention cost, assessment cost, internal failure cost, external failure cost. Qualitative approach with case study method as the research design to find the correlation of quality costs to the companyâs productivity is used in this research.It can be concluded from this research that the reporting of quality cost is proven to be useful in order to improve the productivity of PT Gunawan Dian Jaya Steel. It can come into reality since the company has successfully done the saving of raw materials and controlling the labors in 2010-2012 periods.Keywords: Quality Cost, Prevention Cost, Internal Failure Cost, External Failure Cost